Perceptual-cognitive training of athletes - Faubert, J.; Sidebottom, L. (Journal of Clinical Sport Psychology, 2012)
This present article discusses an approach to training high-level athletes` perceptual-cognitive skills. The intention herein is to (a) introduce concepts in regard to what may be required by athletes to optimally process sports-related visual scenes at the perceptual-cognitive level; (b) present an experimental method of how it may be possible to train this capacity in athletes while discussing the necessary features for a successful perceptual-cognitive training outcome; and (c) propose that this capacity may be trainable even among the highest-level athletes. An important suggestion is that a simple difference between sitting and standing testing conditions may strongly influence speed thresholds with this task, which is analogous to game movement dynamics in sports, indicating shared resources between such high-level perceptual-cognitive demands and mechanisms involved in posture control. A discussion follows emphasizing how a perceptual-cognitive training approach may be useful as an integral component of athletic training. The article concludes with possible future directions.